2009
DOI: 10.1186/1472-6963-9-53
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an area-based intervention on the uptake of maternal and child health assessments in Australia: A community trial

Abstract: Background: Recognition of the importance of the early years in determining health and educational attainment and promotion of the World Health Organization Health for All (HFA) principles has led to an international trend towards community-based initiatives to improve developmental outcomes among socio-economically disadvantaged children. In this study we examine whether, Best Start, an Australian area-based initiative to improve child health was effective in improving access to Maternal and Child Health (MCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Of the 12 initiatives included for analyses, there were five national initiatives: one in Australia, Communities for Children [ 10 , 37 – 39 ]; one in Ireland, the Area Based Childhood (ABC) Programme [ 40 ]; and three in the UK, Sure Start [ 8 , 41 – 46 ], Neighbourhood Nurseries Initiative [ 47 ] and Flying Start [ 48 – 51 ]. There were four state or regional initiatives: one in Australia, Best Start [ 52 – 54 ]; and three in the USA, First Steps (First Steps) to School Readiness [ 55 , 56 ], Smart Start [ 57 , 58 ] and Georgia Family Connection [ 59 ]. The remainder were national or state demonstration projects which were smaller in scope: one in Canada, Toronto First Duty [ 60 – 63 ]; one in Ireland, National Early Years Access Initiative (NEYAI) [ 64 ]; and one in Scotland, Starting Well [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 12 initiatives included for analyses, there were five national initiatives: one in Australia, Communities for Children [ 10 , 37 – 39 ]; one in Ireland, the Area Based Childhood (ABC) Programme [ 40 ]; and three in the UK, Sure Start [ 8 , 41 – 46 ], Neighbourhood Nurseries Initiative [ 47 ] and Flying Start [ 48 – 51 ]. There were four state or regional initiatives: one in Australia, Best Start [ 52 – 54 ]; and three in the USA, First Steps (First Steps) to School Readiness [ 55 , 56 ], Smart Start [ 57 , 58 ] and Georgia Family Connection [ 59 ]. The remainder were national or state demonstration projects which were smaller in scope: one in Canada, Toronto First Duty [ 60 – 63 ]; one in Ireland, National Early Years Access Initiative (NEYAI) [ 64 ]; and one in Scotland, Starting Well [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The remainder were national or state demonstration projects which were smaller in scope: one in Canada, Toronto First Duty [ 60 – 63 ]; one in Ireland, National Early Years Access Initiative (NEYAI) [ 64 ]; and one in Scotland, Starting Well [ 65 , 66 ]. Five initiatives commenced between 1990 and 2000 (Sure Start [ 8 , 41 – 46 ], First Steps [ 55 , 56 ], Smart Start [ 57 , 58 ], Georgia Family Connection [ 59 ], Starting Well [ 65 , 66 ]); five between 2001 and 2009 (Communities for Children [ 10 , 37 – 39 ], Neighbourhood Nurseries Initiative [ 47 ], Flying Start [ 48 – 51 ], Best Start [ 52 – 54 ], Toronto First Duty [ 60 – 63 ]); and two after 2010 (ABC Programme [ 40 ], NEYAI [ 64 ]). Key characteristics of the 12 included initiatives are summarised in Table 2 and the initiatives are described in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…To put some of these findings in context, the World Health Organization (WHO) has promoted the importance of early area-based interventions in health and educational attainment worldwide [34] , leading to community-based initiatives to improve developmental outcomes among socio-economically disadvantaged children [35] – [37] . These initiatives reflect the WHO's principles of the Health for All (HFA) [34] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Best Start project in Australia aims to improve the overall health, development, learning and wellbeing of Victoria's young children and their families in some of the most socially disadvantaged communities through local partnerships and improved service co-ordination [38] . After several years, the findings suggest that improvements in access to services in disadvantaged areas can be achieved by area-based interventions, such as optimising the use of existing resources, and that the potential health benefits of area-based interventions might be better assessed by examining steps along the pathway between intervention and outcome [35] [39] . In the UK, improving education and skills is one of the five priority goals of the National Strategy for Neighbourhood Renewal and the New Deals for Communities Programme.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives such as Sure Start in the UK and Best Start in Australia focus on innovations and extensions of services across a wide front [1,[4][5][6][7]. The evaluation of Sure Start local programs suggested that the program resulted in improved parenting and better social functioning in children among non-teenage mothers but poorer social functioning among the children of teenage mothers and lower verbal ability among children of single parents who did not work [1].…”
Section: Introductionmentioning
confidence: 99%